Vesicle‐mediated secretion of misfolded prion protein molecules from cyclosporin A‐treated cells. Issue 3 (3rd January 2018) - Pan, Ieshita; Roitenberg, Noa; Cohen, Ehud
Abstract : Loss of protein homeostasis is a hazardous situation that jeopardizes cellular functionality and viability Cells have developed mechanisms that supervise protein integrity and direct misfolded molecules for degradation. Nevertheless, subsets of aggregation‐prone proteins escape degradation and form aggregates that can underlie the development of neurodegenerative disorders. In some cases, cells deposit hazardous protein aggregates in desig nated sites, like aggresomes, or secrete them with vesicles. The prion protein (PrP) is an aggregation‐prone membrane‐anchored glycoprotein, whose aggregation causes familial and sporadic, fatal, neurodegenerative dis eases. The proper maturation of PrP is assisted by cyclophilin B, an endoplasmic reticulum‐resident foldase. Ac cordingly, the inhibition of cyclophilins by the drug cyclosporin A (CsA) leads to the accumulation of aggregated PrI and to its deposition in aggresomes. In this study, we asked whether secretion is an alternative strategy that cell adopt to get rid of misfolded PrP molecules and found that, upon treatment with CsA, cells secrete PrP by exosomes, a subtype of secretion vesicles, and by additional types of vesicles. CsA‐induced, PrP‐containing exosomes originate from the endoplasmic reticulum in a Golgi‐independent manner. These findings divulge a new cellular response that is activated upon CsA treatment to secrete misfolded PrP species from the cell and may underlie the spreading of toxic prions among cells and across tissues.—Pan, I., Roitenberg, N., Cohen, E. Vesicle‐mediated secretion of misfolded prion protein molecules from cyclosporin A‐treated cells. FASEB J. 32, 1479‐1492 (2018). www.fasebj.org